The Effect of the Use of Maternity Pillows on the Sleep Quality of Pregnant Women in the 3rd Trimester - Dwi Rahmawati; Yesi Mustikasari (Indonesian Journal of Global Health Research, 2024)
Sleep problems are common in most pregnant women. Physical, psychological and hormonal changes make women more pregnant may suffer from sleep disorders. The impact of sleep disturbances during pregnancy has been linked to an increased risk of premature birth, small babies for gestational age, and high blood pressure. The purpose of this study is to determine the effect of the use of maternity pillows on the sleep quality of pregnant women TM III. The research method used a quasi-design non-equivalent control group experiment. This research was conducted in the city of Jambi. The sampling technique used was purposive sampling with a total sample of 30 samples, 15 experimental groups and 15 control groups. Data analysis using T-Test. The results of the statistical test showed that the p-value was 0.020 <0.05, so it can be concluded that there was a significant difference in sleep quality between pregnant women who were given maternity pillows and pregnant women who were not given maternity pillows.